Cultural diversity versus multiculturalism - Piotr Mazurkiewicz (Chrześcijaństwo-Świat-Polityka, 2020)
The text analyzes the differences between cultural diversity (a state meaning coexistence in one area of different cultures) and multiculturalism (ideology). The latter often tries to impose various forms of mixing cultures from above, proclaiming the positive fruits of such activities. For this reason, it omits the nature of man (objective, universal and common to all people), often turns against the national identity in which he sees an obstacle to the emergence of one global universal culture imposed from above. The creators of this ideology have their own system of values, which they often try to implement without the natural law.